1997
DOI: 10.1080/01688639708403833
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of brain function in adolescent anorexia nervosa before and after weight gain

Abstract: This study assessed brain function in 20 adolescent females with anorexia nervosa (AN) and 20 controls using event-related potentials (ERPs) and a battery of neuropsychological tests. In the AN group, N4 latencies for a nonverbal memory task were significantly longer than for a verbal task, and P3 latencies for the verbal task were significantly longer among anorexics as compared to controls. On the nonverbal task, the AN group failed to show a right > left hemispheric asymmetry for P3 amplitudes which was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 45 publications
(40 reference statements)
9
63
0
5
Order By: Relevance
“…AN patients showed no left-right asymmetry for the P3-amplitude in a nonverbal task. However, neither the studies of Bradley et al (1997) nor Pendleton-Jones et al (1991) found significant differences during neuropsychological examination, that is, no cognitive deficits were detected in AN patients.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…AN patients showed no left-right asymmetry for the P3-amplitude in a nonverbal task. However, neither the studies of Bradley et al (1997) nor Pendleton-Jones et al (1991) found significant differences during neuropsychological examination, that is, no cognitive deficits were detected in AN patients.…”
Section: Introductionmentioning
confidence: 87%
“…On the basis of this assumption, Rovet, Bradley, Goldberg, and Wachsmuth (1988), Pendleton-Jones, Duncan, Brouwers, & Mirsky, (1991), and Bradley et al (1997) conducted neuropsychological studies exploring perceptive-cognitive functions of the right hemisphere in patients with AN. Bradley et al (1997) found changes in event-related potentials (ERPs) during perceptive-cognitive tasks that support the hypothesis of a right parietal dysfunction in patients with AN. Finally, they found significant differences in ERP amplitudes between an AN group and a control group (CO) in verbal as well as in nonverbal tasks.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Findings in clinical populations are inconsistent and limited by small, diagnostically diverse groups and the use of variable outcome measures. [1][2][3] Although most neuropsychological studies in anorexia nervosa (AN) have suggested impairments in higher-level executive, memory, learning, and visuospatial functioning, [3][4][5][6][7][8][9][10][11][12][13] some have not found abnormalities [14][15][16] and others have found superior functioning. [17][18] Some of these studies have lacked a normal control group (NC) 7,12 thereby limiting these findings.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in patients with right hemispheric lesions, lack of concern has been related to an absence of severe depression (Gasparrini, Satz, Heilman, & Collidge, 1978). Rovet, Bradley, Goldberg, and Wachsmuth (1988) and Bradley et al (1997) have reported evidence for atypical lateralization on a right hemisphere task in adolescents with anorexia nervosa. In another study, a lower weight and more severe anorectic symptomatology were correlated with increased left hemispheric activation, whereas weight gain, greater awareness of negative affect, and body part overestimation were related to an increase in right hemispheric activation (Casper & Heller, 1991).…”
Section: Starvation-induced Behavioral Activation May Constitute An Omentioning
confidence: 97%